2022
DOI: 10.1101/2022.08.16.504082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of xanthophyll cycle impacts biomass productivity in the marine microalgaNannochloropsis

Abstract: Life on earth depends on photosynthetic primary producers that exploit sunlight to fix CO2 into biomass. Approximately half of global primary production is associated with microalgae living in aquatic environments. Microalgae also represent a promising source of biomass to complement crop cultivation, and they could contribute to the development of a more sustainable bioeconomy. Photosynthetic organisms evolved multiple mechanisms involved in the regulation of photosynthesis to respond to highly variable envir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…3 ). Similarly, ZEP inactivation under extreme irradiances has been postulated in Nannochloropsis gaditana , an heterokont displaying only the Vx cycle (77). We therefore conclude that in P. tricornutum ZEP3 is active exclusively under non-saturating irradiances to rapidly tune down NPQ, while ZEP2 has properties closer to the ZEP of higher plants and green algae, i.e., a constant activity under all irradiance condition (including darkness and HL) (45, 48, 49, 78).…”
Section: Discussionmentioning
confidence: 78%
“…3 ). Similarly, ZEP inactivation under extreme irradiances has been postulated in Nannochloropsis gaditana , an heterokont displaying only the Vx cycle (77). We therefore conclude that in P. tricornutum ZEP3 is active exclusively under non-saturating irradiances to rapidly tune down NPQ, while ZEP2 has properties closer to the ZEP of higher plants and green algae, i.e., a constant activity under all irradiance condition (including darkness and HL) (45, 48, 49, 78).…”
Section: Discussionmentioning
confidence: 78%
“…So, fast transitions from excess light to low light may result in lower light harvesting capacity due to the persistence of NPQ. Indeed, work in cyanobacteria and plants has shown that the deletion of NPQ capacity (Peers 2015) or tuning of NPQ induction and relaxation can lead to increased biomass accumulation in agricultural situations or dense algal cultures (Kromdijk et al, 2016;De Souza et al, 2022;Perin et al, 2023). We investigated if the level of NPQ could be tuned in Phaeodactylum using a synthetic promoter system.…”
Section: Zep3 Is Required For Maximum Growth Rates In Variable Light ...mentioning
confidence: 99%
“…As an example, the full activation of photoprotection takes some minutes in Nannochloropsis (Perin et al, 2023) and thus microalgae cells moving from the inner, light-limited, layers of photobioreactors to the most external, light-saturated, regions on a milliseconds/ seconds timeframe can experience light damage (Figure 4A).…”
Section: Figurementioning
confidence: 99%